AKTUALISASI NILAI DALAM KONTEKS PENDIDIKAN LUAR SEKOLAH YANG BERBASIS PADA KEARIFAN LOKAL - Septiarti, S Wisni (JIV-Jurnal Ilmiah Visi, 2006)
As a part of national education system, Non Formal Education (NFE) faces challenges in order to empower society and to improve the quality of life. There are neglected values such as social values and local wisdom which decline communication among people. Social values builds up spiritual intelligence for people. NFE organizations implement programs related to them. Integrating those values especially implemented by NFE organizations would shape better future for them as well as make society creative and innovative. It would at last be their self-actualization.